Comparison of static and dynamic shading systems for office building energy consumption and cooling load assessment. Issue 5 (4th June 2018) - De Luca, Francesco; Voll, Hendrik; Thalfeldt, Martin
Abstract : Purpose: Exterior shading devices and dynamic shading systems constitute an efficient way to improve energy efficiency and occupants' comfort in buildings through the reduction of direct solar heat gains and disturbing glare. The purpose of this paper is to analyse the performance of different types of shading systems, fixed and dynamic, and their influence on the energy consumption and cooling loads for an office building located in Tallinn, Estonia. The scope is to determine the most performative configuration for energy consumption and cooling load reduction for office buildings and to provide designers and developers with the necessary knowledge to increase the performance of their buildings. Design/methodology/approach: There are many types of fixed shading devices, most of which use rectangular planar elements, the orientation and layout of which depends on the building location and façade orientation. The dynamic shading systems vary on the base of the building occupancy schedules and occupants' preferences. The paper presents a method to determine the most efficient type and size of fixed shading devices in relation to different windows' size and orientation, and the quantity of windows panes. At the same time the dynamic shading system using a control algorithm developed by the authors is compared. Findings: The results show that solar shading is an efficient way to control the energy consumption of office buildings, though with different efficacy by the static systems depending on orientation, window and shading type. Evidence shows that dynamic blind systems have more uniform performance and usually outperform static shading. Originality/value: The paper compares the performances of different static and dynamic shading devices and systems for the location in Tallinn. The dynamic shading system tested uses a control algorithm developed by the authors. The indications for the energy reduction and cooling loads are a valuable resource for designers and developers to increase the energy efficiency of their buildings.